Tannin-furanic foams used as biomaterial substrates for SERS sensing in possible wastewater filter applications - Gebhard Sabathi; Andreas Reyer; Nicola Cefarin; Thomas Sepperer; Jonas Eckardt; Jonas Neubauer; Fedja Jan Wendisch; Francesco D’Amico; Lisa Vaccari; Gianluca Tondi; Maurizio Musso (Materials Research Express, 2021)
Simple substrates for surface enhanced Raman spectroscopy (SERS), producible in a cost-efficient way, are of growing interest both for scientific and for environmental applications. In this study, we demonstrate the use of three types of bio-based tannin-furanic rigid foams as precursor materials for SERS substrates. Coated with a silver layer, these substrates allowed the detection of several well-known analytes in the mM regime by Raman spectroscopy. Specific optimization of the standard tannin-furanic foam morphology by tuning the chemical synthesis led to a smaller and more homogeneously distributed pore structure, supplying more active hot spot areas. Thus, we obtained a significant increase and a lower relative standard deviation (RSD) of the SERS signal recorded over the mapped SERS substrate area, for several analytes, in particular for Malachite Green dye. This work represents a feasibility study opening several potential applications of this biopolymers in fields such as the detection of water pollutants, virtually combining filtration and SERS capabilities driven by a controlled porosity.